Analisis Hygiene dan Sanitasi dalam Pengolahan Makanan di Kitchen Hotel Rangkayo Basa Padang - Wanda Melisa Nurlita; Yuliana Yuliana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by several problems, namely, employees' health conditions, use of uniform, food processing and conditions of premises and equipment. The aim of this r esearch is to analyze hygiene and sanitation in food processing in the kitchen of the Hotel Rangkayo Basa Padang. This type of research is descriptive qualitative. The type of data used in this research is primary data, namely data obtained from interviews, observation and documentation. Data collection techniques in this research are interviews, observation and documentation. The research instrument used in the research was observation using Aiken V. The results of this research indicate that the analysis of hygiene and sanitation in food processing in the kitchen of the Hotel Rangkayo Basa Padang still needs some evaluation in hygiene and sanitation in food processing. Regarding personal health, personal hygiene, cleanliness of uniforms, employees are expected to have a health check at least once a year, maintain personal hygiene such as cutting their hair and wearing gloves and to be able to wear brightly colored uniforms. Then the equipment storage is still not up to standard and the cleanliness of the equipment is appropriate because there is already a place to wash the equipment and it is washed using a special liquid.